(untitled) (International Journal of Engineering and Computer Science, 2017)
Automatic recognition of geometric and topological features from solid models has a great impact on the various levels of integration. The commercial CAD systems contain information of a component which is not suitable for the use in the next level of product life cycle such as process planning. Various solid modeling software’s hold the design data in their individual files. The structures of the files differ from each other based on the modeling software. To have a common structure which can communicate with various CAD systems a recognition algorithm using any of the neutral file formats is necessary. This paper presents geometric algorithms to recognize features from various 3D CAD models of prismatic parts. The features are recognized by three approaches; Hhint based approach, Volumetric decomposition approach and Hybrid approach. A program in Java is developed to recognize geometric entities, with their directrix contained in a solid model.. The algorithm developed to extract the information from the IGES translator uses an inference engine which can handle complex feature libraries. The algorithm works efficiently for complex models built using volumetric decomposition as well as hybrid of hint based and volumetric decomposition approaches. The model is reconstructed for validation using the recognized entities